The effectiveness of the Barton intervention programme on reading skills of dyslexic students - Mihandoost, Zeinab; Elias, Habibah; Md Nor, Sharifah; Mahmud, Rosnaini (Universiti Putra Malaysia Press, 2012)
The purpose of this study was to determine the effectiveness of the Barton intervention programme on reading skills of dyslexic students. This study used an experimental design. The population included 138 fourth and fifth graders of male and female dyslexic students in Ilam, Iran. A total of 64 dyslexic students were randomly selected and assigned into two groups, namely; the control group and the experimental group. The experimental group received three months of treatment. Pre-test and post-test for the reading skills (i.e. reading recognition, reading fluency and reading comprehension) were carried out on the students to measure their reading skills. The reliability of the reading skills was also confirmed. In addition, the content validity of the scales was investigated using the judgments of 10 psychology experts, whose expert knowledge also confirmed the scales. The analysis of the findings using the Multi-variate Analysis of Variance and the Analysis of Variance showed a significant difference between the control and experimental groups after the treatment of Barton intervention programme, i.e. at p< .000.